TssA: The cap protein of the Type VI secretion system tail. (17th August 2017) - Zoued, Abdelrahim; Durand, Eric; Santin, Yoann G.; Journet, Laure; Roussel, Alain; Cambillau, Christian; Cascales, Eric
Abstract : The Type VI secretion system (T6SS) is a multiprotein and mosaic apparatus that delivers protein effectors into prokaryotic or eukaryotic cells. Recent data on the enteroaggregative Escherichia coli (EAEC) T6SS have provided evidence that the TssA protein is a key component during T6SS biogenesis. The T6SS comprises a trans‐envelope complex that docks the baseplate, a cytoplasmic complex that represents the assembly platform for the tail. The T6SS tail is structurally, evolutionarily and functionally similar to the contractile tails of bacteriophages. We have shown that TssA docks to the membrane complex, recruits the baseplate complex and initiates and coordinates the polymerization of the inner tube with that of the sheath. Here, we review these recent findings, discuss the variations within TssA‐like proteins, speculate on the role of EAEC TssA in T6SS biogenesis and propose future research perspectives. Abstract : In the environment, bacteria have to cope with other microbial species and therefore have evolved anti‐microbial mechanisms. The bacterial Type VI secretion system (T6SS) transports toxins into bacterial and/or eukaryotic cells using a contractile mechanism. At the architectural level, the T6SS could be viewed as a nano‐speargun assembled in the bacterial cytoplasm and anchored to a trans‐envelope complex. We describe and speculate on recent findings demonstrating that the TssA subunit is involved in the different stages of T6SS biogenesis.